2014
DOI: 10.1139/cjc-2014-0191
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of phenol and hydroxyl radical reaction mechanism in aqueous medium by the DFT/B3LYP/6-31+G(d,p)/CPCM model

Abstract: Four different possible reaction pathways of phenol and hydroxyl radical reaction were investigated theoretically by density functional theory (DFT) B3LYP with the 6-31+G(d,p) calculations under the conductor-like polarized continuum model (CPCM). According to frontier molecule orbital theory, both the highest occupied orbital and lowest occupied orbital of phenol (25th orbital) showed –602.79 and –43.53 kJ mol−1 molecular orbital energies, respectively. This resulted in a 559.27 kJ mol−1 relative energy gap. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…Except for H-abs, the rate constants of the other ve reaction pathways in the aqueous phase were much higher than in the gas phase. Furthermore, the hydrogen abstraction rates of benzoic acid were much higher than for phenol (1.60 Â 10 À16 cm 3 per molecule per s), 49 since benzoic acid has an electronic withdrawing group, while phenol contains an electron donor group. 50 San et al calculated the reaction rate constants of benzoic acid with hydroxyl radical reaction in the aqueous phase, and the reaction rates were 8.38 Â 10 À11 , 4.20 Â 10 À8 , 1.65 Â 10 À20 , 5.08 Â 10 À24 cm 3 per molecule per s for meta addition reaction, ortho addition reaction, para addition reaction, and H-abs, respectively.…”
Section: Reaction Rate Constantsmentioning
confidence: 92%
“…Except for H-abs, the rate constants of the other ve reaction pathways in the aqueous phase were much higher than in the gas phase. Furthermore, the hydrogen abstraction rates of benzoic acid were much higher than for phenol (1.60 Â 10 À16 cm 3 per molecule per s), 49 since benzoic acid has an electronic withdrawing group, while phenol contains an electron donor group. 50 San et al calculated the reaction rate constants of benzoic acid with hydroxyl radical reaction in the aqueous phase, and the reaction rates were 8.38 Â 10 À11 , 4.20 Â 10 À8 , 1.65 Â 10 À20 , 5.08 Â 10 À24 cm 3 per molecule per s for meta addition reaction, ortho addition reaction, para addition reaction, and H-abs, respectively.…”
Section: Reaction Rate Constantsmentioning
confidence: 92%
“…The HOMO/LUMO analysis will be helpful to determine whether the frontier orbitals between the BPF molecules and HO· match well. The previous study showed that the singly occupied molecular orbital (SOMO) of HO· is characteristic of π‐type orbital. From Supporting Information Figures S4 and S5, it can be found that both the HOMO and LUMO isosurfaces near the hydroxyls and benzenes in BPF molecules are π‐type orbitals and symmetrical to the SOMO of HO·.…”
Section: Resultsmentioning
confidence: 99%
“…For clarity, the Fukui function for radical attack was mapped onto the total electron density of each BPF molecule (Figure , isovalue = 0.0028 a.u.). The previous study showed that in phenol derivatives containing one phenolic ring, the C 2 , C 3 ,C 4 , C 5 , and C 6 (the number rules can be found in Figure ) are the active sites to accept the HO· attack. Here, based on the Fukui function analysis, it can be said that for most of the BPF molecules, the C 2 , C 3 , C 5 , and C 6 are active sites (the dark blue regions).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that this functional gives reasonable results for similar radical based studies. 23,39,[50][51][52][53] Additional calculations for the reaction mechanisms were performed using the ωB97XD 54 functional which has also been shown to give satisfactory results. [55][56][57][58] For the light atoms the 6-311+G(d,p) basis sets 59 were used, whereas LANL2TZ effective core potential basis set 60 was used for the iridium atom of the photocatalyst to account for relativistic effects.…”
Section: Methodsmentioning
confidence: 99%